Effects of Information and Communication Technology Use on the Executive Function of Older Adults without Dementia: A Longitudinal Fixed-Effect Analysis - Hamin Lee; Sangmi Park; Seungho Han; Hyeon Dong Lee; Ickpyo Hong; Hae Yean Park (Annals of Geriatric Medicine and Research)
Background Impaired executive function is common in older adults. This study examined the causal relationship between the use of information and communication technology (ICT) and executive function in older adults over time. Method This study performed a secondary analysis of data from four waves (2016–2019) of the National Health and Aging Trends Study. A fixed-effect analysis was conducted to examine the effects of ICT on the executive function of older adults without dementia aged ≥65 years. This study analyzed data from 3,334 respondents. Results We observed significant positive effects of ICT use on executive function over time (standardized β=0.043–0.045; 95% confidence interval, 0.001–0.043; p<0.05). Conclusion The current findings support the use of ICT as a protective approach to prevent decline in executive function in community-dwelling older adults.